LEADERSHIP OF THE HEAD MADRASAH IN BUILDING THE SCHOOL CLIMATE IN MADRASAH ALYAH AL-WASHLIYAH 49 PASAR LEMBU, AIR JOMAN DISTRICT, ASAHAN REGENCY - Syafaruddin Syafaruddin; Syamsu Nahar; Imran Imran (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This research analyzes the leadership of the madrasa principal in building a school climate, and the example of the madrasa principal in building a school climate in Madrasah Aliyah Al-Washliyah 49 Pasar Lembu, Air Joman District, Asahan Regency.This type of research is a qualitative research approach, through observation, interviews, and document review. This method is used for several reasons, first, adapting this method is easier when dealing with reality. Second, this method presents directly the nature of the relationship between the researcher and the respondent. Third, this method is more sensitive and more adaptable to the many sharpening of joint influences on the patterns of values encountered. The interview targets/respondents in this study included the head of the madrasa, the deputy head of the madrasa, and teachers and all madrasah residents. The formulation of the research problem is 1)How is the leadership type of the madrasa principal in building the school climate in Indonesia? Madrasah Aliyah Al-Washliyah 49 Pasar Lembu, Air Joman District, Asahan Regency; 2)How is the exemplary leadership of the madrasa principal in building a school climate?in Madrasah Aliyah Al-Washliyah 49 Pasar Lembu, Air Joman District, Asahan Regency.The results of the research findings include 1) the type of leadership of the madrasa principal is democratic and fatherly, 2) the exemplary madrasa principal applied includes providing maximum service to all school members.